2018
DOI: 10.1021/acsami.8b09442
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Band High-Sensitivity ZnO Colloidal Quantum Dots/Self-Assembled Au Nanoantennas Heterostructures Photodetectors

Abstract: Tunable plasmonic resonance induced by the collective oscillation of the electrons on metallic nanostructures can excellently enhance the light response of ZnO films, which provides an effective way to break through the limitation of the performance of ZnO photodetectors. Here, broad-band high-performance ZnO/Au heterostructures photodetectors with various morphologies of self-assembled Au nanoantennas are fabricated via a facile approach under the spin-coated ZnO colloidal quantum dots films. With a systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 59 publications
1
49
0
Order By: Relevance
“…In specific, the photocurrent of bare GaN, Ag, and Au reached up to 3.56 × 10 –4 , 9.97 × 10 –4 , and 1.61 × 10 –3 A, respectively, at 0.1 V and 10.36 mW mm −2 . The integration of Ag and Au NPs on the bare GaN photodetector demonstrated a strong contribution toward photocurrent enhancement due to the LSPR effect [ 29 , 42 ]. At the same time, it was also observed that the Au NPs induced much larger photocurrent as compared to the Ag NPs, which suggests the morphological and elemental dependence of LSPR in the photocurrent enhancement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In specific, the photocurrent of bare GaN, Ag, and Au reached up to 3.56 × 10 –4 , 9.97 × 10 –4 , and 1.61 × 10 –3 A, respectively, at 0.1 V and 10.36 mW mm −2 . The integration of Ag and Au NPs on the bare GaN photodetector demonstrated a strong contribution toward photocurrent enhancement due to the LSPR effect [ 29 , 42 ]. At the same time, it was also observed that the Au NPs induced much larger photocurrent as compared to the Ag NPs, which suggests the morphological and elemental dependence of LSPR in the photocurrent enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…The R is defined as the ratio of photocurrent generated to illuminated optical power intensity and expressed as Eq. 2 [29]:…”
Section: Uv Photoresponse Of Monometallic Ag and Au Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photoresponse of the ZnO QD-based photodetectors can also be increased with the aid of localized surface plasmon resonance (LSPR). [160][161][162] In this technique, novel metal nanoparticles are fabricated over the sensing material. In such a case, a nearsurface electric eld is formed due to the collective oscillation of electrons on the surface nanoparticles, which ultimately increases the absorption of light.…”
Section: Optoelectronicsmentioning
confidence: 99%
“…Hybrid Architecture Photodetectors Fabrication : ZnO colloidal quantum dots (CQDs) were initially synthesized by the solvothermal method, and spin‐coated on glass substrates. Briefly, 1.29 g of potassium hydroxide (KOH, 85%, Aladdin, CAS: 1310‐58‐3) was dissolved into 23 mL of methanol, and then gradually dropped into 126 mL zinc acetate (2.94 g, Zn(CH 3 COO) 2 , 99.99%, Aladdin, CAS: 5970‐45‐6) methanol solution (CAS: 67‐56‐1).…”
Section: Methodsmentioning
confidence: 99%